Representasi Harga Diri Orang Madura di Jawa (Studi tentang Wanita Madura di Gondanglegi Kulon Kecamatan Gondanglegi Kabupaten Malang) - Harun Ahmad; Ali Badar; Yahmin Yahmin (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2018)
Honor and esteem in society Madura considered highly sensitive, and drawn on the term “lebbi bagus pote tolang etembang pote mata” (preferably white bones of the white of the eye, which means it’s better to die than live with the shame). After migration to Java Madura people, have consequences on the socio-cultural adaptation of the local area through associations and everyday social relations. This phenomenon is interesting to study how the traditions and customs of Madura in the Java community, especially with regard to self-esteem, which is represented in its view of women. The experiment was conducted in the village of Gondanglegi Kulon Gondanglegi District Malang Regency. Data mining techniques used were interviews, participant observation, and documentation. Research to get the fndings: (1) Wife depending husband; (2) Women’s advocate family economy; (3) Regardless, the woman returned to the kitchen; (4) Self-esteem is the Madura is Islam with slogan Madura-Mecca-Medina; (5) Haji improve self-esteem; (6) The woman is the family honor in a religious context. From the fndings of this study indicate that the Madurese in Java in accordance with their ancestral cultures on the island of Madura but for its application has undergone a unique adaptation that means being on a problem in life is largely determined by the surrounding environment. Moreover, Madurese in Java sees problems related to women who are still considered family pride is not easy anymore to violence even in the last 10 years there were no cases of violence because of the issue of women.